PENENTUAN NILAI PREMI ASURANSI PERTANIAN BERBASIS HARGA INTERNASIONAL MENGGUNAKAN MODEL MEAN REVERSION DENGAN MUSIMAN - ANDIKA, I NYOMAN BRYAN; DHARMAWAN, KOMANG; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 12 No 1 (2023)DO - 10.24843/MTK.2023.v12.i01.p401, 2023)
The seasonal cycle causes cocoa price movements in the international market to fluctuate. This certainly affects the development of cocoa prices at the producer level, causing uncertainty about the prices received by farmers. International price-based agricultural insurance is an alternative to protect farmers against global price fluctuations. Compensation is given if the global price of cocoa falls below the agreed trigger value. This study aims to calculate the fair premium value for agricultural insurance based on international prices for cocoa in the Tabanan Regency, Bali, which was simulated using a mean reversion model with seasonality. To perform the simulation, the first step is to estimate the parameters of the seasonal model and the mean reversion model. Next, simulate the international price of cocoa. Then, determine the trigger value based on the percentile of the simulation data. Finally, calculate the premium value using the cash-or-nothing put option with the Black-Scholes model. The results show that the premium value which is considered fair lies between 5,77% to 11,08% of the insured value.